2017
DOI: 10.1111/eufm.12116
|View full text |Cite
|
Sign up to set email alerts
|

How Useful Is Basel III's Liquidity Coverage Ratio? Evidence From US Bank Holding Companies

Abstract: This paper approximates a construction of Basel III's Liquidity Coverage Ratio (LCR) for US bank holding companies. This study examines (i) the LCR's marginal contribution to a firm's systemic risk and (ii) whether the LCR can predict ex ante which banks are most exposed to systemic losses in a true systemic event. Panel regressions from 2002 to 2015 show that the LCR is associated with lower relative systemic risk, measured by ΔCoVaR. The LCR may be used conjunctively with marginal expected shortfall to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…In line with this result, Giordana and Schumacher (2017) indicated that the liquidity requirements of the Basel III decrease the probability of default for banks. Therefore, banks tend to have lower risk when they have a high level of liquid assets, thus enhancing their stability (Du, 2017;Dietrich et al, 2014). In this context, Yan et al (2012) and Al-Hares et al (2013) found that the liquidity regulation played a positive significant role to absorb any financial crises, resulting in increased stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this result, Giordana and Schumacher (2017) indicated that the liquidity requirements of the Basel III decrease the probability of default for banks. Therefore, banks tend to have lower risk when they have a high level of liquid assets, thus enhancing their stability (Du, 2017;Dietrich et al, 2014). In this context, Yan et al (2012) and Al-Hares et al (2013) found that the liquidity regulation played a positive significant role to absorb any financial crises, resulting in increased stability.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical results showed that the LCR benefitted banks in the emerging markets, including raising their profitability. Du (2017) tested how the systemic risk of U.S. bank holding companies would be reduced after applying the LCR of the Basel III. The sample period covered 2002 to 2015 and consisted of 761 banks.…”
Section: The Interplay Between the Liquidity Coverage Ratio Requirements And Banks' Profitabilitymentioning
confidence: 99%
“…Even if modern deposit guarantee systems have made traditional bank runs more or less obsolete, Du (2017) proposed that the financial crisis of 2007-2008 was actually a bank run in a more modern sense of the concept because modern financial institutions currently rely heavily on short-term funding. Huang and Ratnovski (2011) also showed that in an environment with a costless but noisy signal, short-term wholesale financiers may suddenly withdraw heavily, i.e., run, hence triggering liquidation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, we contribute by discussing the fragility of the current financial and economic systems mentioned above and in the literature review. Moreover, instead of using data on U.S. banks (as for example in DeYoung et al 2018, Hong et al, 2014, and Du 2017, we use a large dataset on Western European banks, including both the commercial banks and the large stakeholder banking sector of Western Europe. Likewise, the sample period from 2005-2017 extends that of Caporale et al (2012), who used a sample covering the 2000-2007 period.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show that repo markets' instability contributed to the global financial crisis (GFC) (Adrian & Shin, 2010; Copeland et al, 2014; Du, 2017; Gorton & Metrick, 2012; Gorton, 2009; Martin et al, 2014). For instance, Lehman Brothers engaged widely in window dressing practices (so called “repo 105”) to hide its actual leverage figure by accepting a relatively high (5%) haircut.…”
Section: Introductionmentioning
confidence: 99%